Textiles : concepts and principles - Elsasser, Virginia Hencken, ....- (New York : Fairchild Books, 2010)
This clear and concise book focuses on the interrelationship of textile components to help students understand and predict textile properties and performance. Intended for undergraduate programs of colleges and universities that focus on fashion merchandising, fashion design, and interior design, Textiles: Concepts and Principles provides a thorough introduction to the fundamentals of textiles.
Includes index.
Keywords: Textile fabrics; Textile fibers